Beacon‐based routing protocols for underwater acoustic sensor networks. (4th August 2017) - Tariq, Moeenuddin; Abd Latiff, Muhammad Shafie; Ayaz, Muhammad; Abbas, Muhammad Zahid
Summary: Underwater Acoustic Sensor Networks (UW‐ASN) are provisioned with limited bandwidth, long variable propagation delay, limited available energy, highly unreliable acoustic channels, and random node mobility. Consequently, efficient data routing between source destination pair requires UW‐ASN to apply a technology different than terrestrial networks. For the past few years researchers have proposed many robust and efficient routing protocols for UW‐ASN, thus reviewing the challenges posed by stringent underwater environment. These protocols can be broadly categorized into localization based and localization‐free protocols. This paper presents a critical review of beacon‐based localization‐free routing protocols and suggest possible solution to improve the working of studied beacon based protocols. This work categorizes beacon based protocols into hop‐by‐hop, end‐to‐end, single, and multiple parameters based forwarding protocols. This categorization will help to differentiate and identify the requirements for the development of new beacon‐based protocols. Finally, this paper presents performance comparison based on simulation results and outlines the research gap and future directions. Abstract : This manuscript is about beacon‐based underwater routing protocols, and for this purpose, a taxonomy of available protocols is provided to understand their working behavior and identify their requirements. All the significant beacon‐based underwater routing protocols proposed to date are critically analyzed by considering various metrics, and suggestions have been made to improve their performance. Furthermore, relevant research issues are highlighted that should be considered for the development of similar protocols.